People's budget : an illustrative exercise using participatory tools - Institute for Development Policy Analysis and Advocay (Dhaka, Bangladesh); Proshikhsan Shikhsa Kaj (Organization : Bangladesh); Shamunnay (Organization : Bangladesh) (Dhaka : University Press, 2002)
With reference to Bangladesh written from the perspective of the pro-poor.
Includes bibliographical references (pages [265]-269).
BIED
Complimentary copy from BIED
Donated by Akbar Ali Khan
Keywords: Budget -- Bangladesh; Poor -- Bangladesh; Bangladesh -- Appropriations and expenditures